Risk Management in Financial Institutions: A Replication - GUEST, PAUL M. (Journal of Finance, 2021)
ABSTRACT Rampini, Viswanathan, and Vuillemey (RVV) show empirically that net worth drives hedging. I identify discrepancies to which RVV's key findings are not robust: the positive correlation between net worth and hedging is not independent of institution size, house price decline shocks to net worth (which RVV use for identification) have mixed effects on hedging that are not robust across alternative specifications, and the treatment effects on net worth and hedging are not increasing in real estate exposure, inconsistent with a causal explanation. Overall, my analysis does not support the conclusion of RVV that higher net worth causes more hedging.